2003
DOI: 10.1097/01.jcp.0000095350.32154.73
|View full text |Cite
|
Sign up to set email alerts
|

5-HTTLPR Polymorphism of the Serotonin Transporter Gene Predicts Non-Remission in Major Depression Patients Treated With Citalopram in a 12-Weeks Follow Up Study

Abstract: In the context of a long term follow-up study, we analysed the possible implication of the 5-HTTLPR polymorphism at the serotonin transporter gene in clinical response and remission of major depressive patients treated with citalopram. The sample consisted of 131 patients, all of Spanish origin, diagnosed according to DSM-IV criteria. A 21-item Hamilton Depression Rating Scale (HDRS) was used to evaluate severity of the symptoms during the follow-up and to determine clinical response and remission condition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
2
4

Year Published

2005
2005
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(89 citation statements)
references
References 25 publications
6
77
2
4
Order By: Relevance
“…6 In contrast to these findings, the majority of previous studies investigating the inheritance of 5-HTTLPR genotype on antidepressant efficacy have found the short allele to be associated with reduced antidepressant response. [7][8][9][10][11][12][13][14][15][16] This may be explained by a number of variables that differ between the studies. First, variation in the criteria used to measure response has differed between studies, with a reduction of 50% or more from baseline Hamilton Depression Rating Scale (HAMD) scores used in certain studies, 4,5,7,13,[15][16][17] but an HAMD score of 8 or less was used to determine response in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…6 In contrast to these findings, the majority of previous studies investigating the inheritance of 5-HTTLPR genotype on antidepressant efficacy have found the short allele to be associated with reduced antidepressant response. [7][8][9][10][11][12][13][14][15][16] This may be explained by a number of variables that differ between the studies. First, variation in the criteria used to measure response has differed between studies, with a reduction of 50% or more from baseline Hamilton Depression Rating Scale (HAMD) scores used in certain studies, 4,5,7,13,[15][16][17] but an HAMD score of 8 or less was used to determine response in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the second study found that the SS genotype or S allele was nonsignificantly associated with decreased risk of depression in the British population [140]. A nonsignificant protective effect of the S allele was observed among Spaniards [109] and Germans [141,142]. Five studies of whites [143][144][145][146][147] found no substantial relationships between the 5-HTTLPR genotype and major depressive disorder.…”
Section: Major Depressive Disorder and 5-httlpr Polymorphismmentioning
confidence: 93%
“…Due to its potential involvement in psychiatric diseases like depression, BDNF became a major target in research. A functional polymorphism of the BNDF Val66Met influences and reduces trafficking and secretion of BNDF protein in the brain and is thought to be associated with low BDNF levels in major depressive disorder [108][109][110]. Some did associate the BDNF Val66Met genotype with depression [111], but other groups found only weak or no associations [112][113][114][115].…”
Section: Genetic Epidemiologymentioning
confidence: 99%
“…Hardy-Weinberg equilibrium was examined in studies where genotype frequencies were included. 9,[15][16][17][18][19][20][21][22][23][24][25] Given the lack of unequivocal data for 5-HTTLPR genotype pooling, we tested both dominant and recessive hypotheses: l/l versus l/s-s/s and l/l-l/s versus s/s. Outcome was defined with three phenotypes: remission rate, response rate, and response rate within 4 weeks.…”
Section: Methodsmentioning
confidence: 99%